Book Review: Principles of Contemporary Corporate Governance - Brown, David (Victoria University of Wellington Law Review, 2005)
This article is a book review of Jean Jacques du Plessis, James McConvill and Mirko Bagaric Principles of Contemporary Corporate Governance (Cambridge University Press, Melbourne, 2005) (395 + xxii pages). Broader theoretical and policy approaches were being taken in relation to corporate governance regulation. This meant that there was a growing need for a framework of principles within which students and scholars can approach the subject, and policymakers and interested parties can operate. The authors of the book aim to extract and evaluate such core principles. Brown argues that the title of the book both understates and overstates what it does. The book does contain principles of corporate governance, but Brown doubts whether the subject matter was demystified and fails to explore certain hot topic issues. However, the book also discusses regulation and practice of corporate governance and is imbued throughout with the authors’ views as to the scope and future of corporate governance regulation. Brown ultimately concludes that the book is a welcome and timely resource in terms of coverage and detail.